1981
DOI: 10.1177/29.1a_suppl.6270206
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic Determination of Neurotransmitter Receptor Distributions in the Cerebral and Cerebellar Cortices,

Abstract: Light microscopic autoradiographical localization of drug and neurotransmitter receptors provides investigators with a tool to determine the sites of drug action with a high degree of anatomical resolution. In the cortex, where there is a distinct laminar organization, the differential distribution of receptors can be determined. We have found that differences in the density of specific receptors exist between layers of the cerebral cortex. Our observations include the localization of muscarinic cholinergic, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

1982
1982
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(3 citation statements)
references
References 30 publications
(20 reference statements)
1
1
1
Order By: Relevance
“…(The proenkephalin-immunostained bipolar-like cells and some of the multipolar cells extend their dendrites into layer I.) However, an alternative autoradiographic technique has localized mu-type ligands to layer IV in rats (Goodman et al, 1980;Wamsley et al, 1981), where little or no opioid peptidergic-ir in cells or fibers was found in the present study. Other opioid receptor subtypes have been localized with a predominance in different cortical layers (delta subtype- Goodman et al, 1980;Lewis et al, 1983; kappa subtype- Foote and Maurer, 1982) or different regions (kappa subtype- Goodman and Snyder, 1982;sigma subtype-Quirion et al, 1981;Zukin et al, 1983).…”
Section: Discussioncontrasting
confidence: 65%
“…(The proenkephalin-immunostained bipolar-like cells and some of the multipolar cells extend their dendrites into layer I.) However, an alternative autoradiographic technique has localized mu-type ligands to layer IV in rats (Goodman et al, 1980;Wamsley et al, 1981), where little or no opioid peptidergic-ir in cells or fibers was found in the present study. Other opioid receptor subtypes have been localized with a predominance in different cortical layers (delta subtype- Goodman et al, 1980;Lewis et al, 1983; kappa subtype- Foote and Maurer, 1982) or different regions (kappa subtype- Goodman and Snyder, 1982;sigma subtype-Quirion et al, 1981;Zukin et al, 1983).…”
Section: Discussioncontrasting
confidence: 65%
“…The response to OX0 in layers IV and V coincides with the laminar distribution of cholinoceptive cells (Krnjevid and Phillis, 1963a, b), the concentration of acetylcholinesterase (Beesley and Emson, 1975), and the densities of high affinity muscarinic binding sites in the neocortex (Wamsley et al, 1981;J. K. Wamsley, unpublished data).…”
Section: Discussionsupporting
confidence: 52%
“…Quantitative receptor autoradiography using emulsion and tritium-sensitive film has been de-scribed for [3H]QNB and other neurotransmitter ligands and provides a higher level of resolution than is possible with homogenate binding studies 13,21,23,26,30,34,35,38,39. Direct comparison of quantitative autoradiographic data and homogenate binding demonstrated consistent, significant absolute differences between the two methods.…”
Section: Discussionmentioning
confidence: 99%